Culture and globalisation: an analysis of cultural globalisation in modern era - Tsanwani, A.; Mulaudzi, T. P.; Raselekoane, N. R. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
The purpose of this paper is to analyse the impact of global-culture in developing countries. The paper seeks to explore the challenges brought by globalisation to different states and their societies. The main objective being to evaluate the extent to which globalisation impacts different cultures, identify the causes of dominance of other cultures and also propose measures to be taken to strike a balance between cultures of different nations. To achieve the objectives of this; the paper relied on both primary and secondary sources to collect data. The borderless world brought by the system of globalisation is meant to promote the fiscal, cultural and political flows without any restrictions. In the other hand, borderless world is promoting dominance of some cultures over others. African states seem to be in a state of confusion brought by the system of globalisation. Western states seem to be imposing their cultures which contradict values and norms of developing countries. Globalisation is localizing everything economy, politics and culture. This is declaring war against different societies. The questions brought forward are: which culture is the best? How can an individual protect or preserve his or her own culture? Is there any bad culture? Is globalisation wrong? Fundamentalists face a challenge of having to come to grips with the notion of globalisation, have to strike a balance between maintaining cultural integrity and tradition, have to absorb changes associated with globalisation of the world. The main challenge being that, it seems individual members have no choice but to adjust to modern and its accompanying changes. Globalisation is a paradigm shift from which there is no escape; the shift which affects lifestyle, value systems, cultural and mental attitudes towards local, national and the universe. The process has de-territorialised culture and politics, but at the same time has intensified cultural politics in many countries. Identities are constructed in dynamic process and assume multiple forms that permit individuals and societies to uphold both cultural diversity and global norms, such as human rights and democratisation.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Globalisation; Culture; Tradition; Fundamentalists; Identity; Culture and globalization; Culture; Globalization -- Social aspects -- Developing countries; Fundamentalists; Identity